PWE-102 Urinary 1h nuclear magnetic resonance spectroscopy profiling in hepatoecellular carninoma in a bangladeshi cohort corroborates a urinary metabolic fingerprint for liver cancer. (22nd June 2015) - Cox, IJ; Podrini, C; Markwick, LJ; Williams, R; Al-Mahtab, M; Akbar, F; Rahman, S; Islam, A; Montagnese, S; Crossey, M; McPhail, M; Taylor-Robinson, SD
Abstract : Introduction: Urinary metabolic profiling using nuclear magnetic resonance (NMR) spectroscopy has an increasing role in both understanding the pathophysiology of cirrhosis, the development of hepatocellular cancer (HCC) and the discrimination of malignant and non-malignant hepatic nodules arising on the background of cirrhosis. Clinical cohorts from Egypt, 1 Nigeria 2, 3 and The Gambia 2 have been studied and consensus is emerging for an identifying urinary fingerprint of HCC. The aim of this study was to establish if a similar urinary NMR fingerprint for HCC could be identified in a Bangladeshi cohort. Method: Urine samples were collected with local research ethics approval and informed consent from 21 Bangladeshi patients with HCC diagnosed by ultrasound and standard clinical tests. Proton ( 1 H) NMR spectra were acquired using a JEOL ECP 500 11.7 Tesla spectrometer with a pulse-collect sequence and pre-saturation of the water signal. The HCC urinary 1 H NMR spectral profiles were compared to 18 archived urinary 1 H NMR spectral profiles from Western European healthy subjects. Processed 1 H-NMR spectroscopy data underwent further analysis with principal component analysis (PCA). Results: PCA illustrated that the urinary 1 H NMR spectral profiles from HCC subjects differed to the control cohort across range of metabolites, including reduced hippurate and creatinine levels but increased creatine levels. These findings are consistent with the published findings from the studies of various African populations. 1, 2, 3 Conclusion: Urinary metabolite changes continue to be identified in subjects with HCC, which may be consistent with the diverse effects of HCC on both human physiology and gut bacterial action. Our studies further support the observation of candidate urinary biomarkers of HCC which may aid the development of a simple urinary screening test. Disclosure of interest: None Declared. References: Shariff MI, et al . Urinary metabolic biomarkers of hepatocellular carcinoma in an Egyptian population: a validation study. J Proteome Res. 2011;10:1828–1836 Ladep NG, et al . Discovery and validation of urinary metabotypes for the diagnosis of hepatocellular carcinoma in West Africans. Hepatology 2014;60:1291–1301 Shariff MI, et al . Characterization of urinary biomarkers of hepatocellular carcinoma using magnetic resonance spectroscopy in a Nigerian population. J Proteome Res. 2010;9:1096–1103